Placental histologic patterns and neonatal seizure, in preterm premature rupture of membrane. (3rd April 2017) - Ko, Hyun Sun; Cheon, Ju Young; Choi, Sae Kyung; Lee, Hye Won; Lee, Ahwon; Park, In Yang; Shin, Jong Chul
Abstract: Objective : To investigate the relationship between placenta and perinatal outcomes, in preterm infants born to mothers with preterm premature rupture of fetal membrane (PPROM). Methods : We report detailed histology of placentas and perinatal outcomes of infants from 79 PPROM pregnancies. Placental histologic pattern and adverse perinatal outcomes were assessed by logistic regression, adjusting for gestational age at birth, birth weight and interval from rupture of membrane to delivery. Results : Mean gestational age at membrane rupture was 29.5 ± 3.4 weeks. The incidence of histologic chorioamnionitis (HCA), fetal inflammatory response (FIR) and vascular thrombotic abnormalities in placental histologic examination were 63.3, 25.3 and 78.5%, respectively. Neonates with FIR showed significantly higher incidence of periventricular leukomalacia (PVL) (85% versus 59.3%, p = 0.0364) at brain ultrasonography, than neonates without FIR, in univariate analysis, but not in logistic regression analysis. In logistic regression analysis, the odds ratio of low Apgar score at 1 min in the neonates with clinical chorioamnionitis was 5.009 (95% CI, 1.242–20.195). The odds ratio of neonatal seizure in the neonates with FIR and vascular thrombotic problem was 7.486 (95% CI, 1.617–34.653). Conclusions : Our findings support the association between FIR with vascular thrombotic problem in placenta and neonatal seizure, in pregnancies with PPROM.